Exceptional strength-ductility synergy of additively manufactured CoCrNi medium-entropy alloy achieved by lattice defects in heterogeneous microstructures. (10th November 2022) - Wang, Jianying; Zou, Jianpeng; Yang, Hailin; Zhang, Lijun; Liu, Zhilin; Dong, Xixi; Ji, Shouxun
Highlights: Giant strengthening in SLMed CoCrNi alloys by subsequent deformation and annealing. CoCrNi alloy delivers yield strength of 1161.6 MPa and strain of 31.5%. The refined hierarchical microstructure and lattice defects result in high strength. Abstract: The selective laser melting (SLM) with subsequent cold rolling and annealing is used to produce high-density lattice defects and grain refinement in the CoCrNi medium-entropy alloys (MEAs). The superior comprehensive mechanical properties have been achieved in the as-SLMed CoCrNi alloy after rolling and annealing. The as-SLMed alloys delivered the yield strength of 693.4 MPa, the ultimate tensile strength of 912.7 MPa and the fracture strain of 54.4%. After rolling with 70% reduction in thickness and annealing at 700 °C for 2 h. the yield strength, ultimate tensile strength and fracture strain reached 1161.6 MPa, 1390.8 MPa and 31.5%, respectively. The exceptional strength-ductility synergy is mainly attributed to the refined hierarchical microstructures with coarsening grains at a level of 30 µm and ultrafine grains at a level of 1 µm, and the heritage of dislocation-formed sub-grains and other lattice defects. This investigation demonstrates that the SLM with subsequent rolling and annealing is beneficial to fabricate high strength and ductile MEAs with single face-centered cubic (fcc) structure.